Simulation of Drill Cuttings Dispersion and Deposition in South China Sea - Hock, Lye Koh; Su Yean, Teh (2011)
Drill cuttings with various characteristics and sizes are produced in any offshore oil and gas exploration and production (EP) drilling of the seabed.